Airway clearance by exercising in mild cystic fibrosis (ACE-CF): A feasibility study. (September 2018) - Ward, Nathan; Stiller, Kathy; Rowe, Hilary; Morrow, Scott; Morton, Judith; Greville, Hugh; Holland, Anne E.
Abstract: Background: People with cystic fibrosis (CF) are encouraged to perform airway clearance techniques on a daily basis. Whilst several short-term studies support a potential role for exercise as an airway clearance technique, to date no medium to longer term studies have investigated the use of exercise as a stand-alone airway clearance technique. Objective: To determine the feasibility of a protocol investigating the use of exercise as a stand-alone form of airway clearance in adults with CF. Methods: Adults with CF and a FEV1 ≥ 70% predicted were eligible. After a four week wash-in period of daily positive expiratory pressure (PEP) and exercise, adherent participants were randomised to either daily PEP plus exercise or exercise-only for three months. Pre-specified thresholds for feasibility for the primary outcomes were rates of recruitment ≥30%, randomisation ≥80% and completion ≥80%. Secondary outcomes included respiratory function tests, respiratory exacerbation rate and health-related quality of life. Results: Of the 57 eligible patients identified, 17 were recruited (30%). After the wash-in period, 13 of the 17 participants (76%) were randomised and all 13 (100%) completed the final assessment. The median (IQR) change in FEV1 (L) over the intervention period was 0.00 (−0.08 - 0.15) L for the PEP plus exercise group and −0.03 (−0.19 - 0.13) L for the exercise-only group. Conclusion: The study achieved its a priori target feasibility rates for recruitment and completion but failed to meet the randomisation target rate. Changes in lung function and quality of life were similar between groups. Further refinement of the protocol may be required prior to expansion to a multi-centred trial. Highlights: The first medium-term study to investigate exercise as a form of airway clearance. The recruitment rate target was achieved but not the target randomisation rate. Lung function and quality of life changes were similar between groups. A larger multi-centre trial is required.